Preferences for thromboprophylaxis in the intensive care unit: An international survey - Heijkoop, Èmese Robin Hélène; Keus, Frederik; Møller, Morten Hylander; Perner, Anders; Morgan, Matthew; Abdelhadi, Adel; Al Shirawi, Nehad Nabeel Mohamed; Al-Fares, Abdulrahman A; Alshamsi, Fayez; Ananthan, Prakkash Parangi; Andreasen, Anne Sofie; Anstey, Matthew H; et al. (Acta anaesthesiologica Scandinavica, 2025)
BACKGROUND: Venous thromboembolism (VTE) is a frequent complication in critically ill patients, who often have multiple risk factors. Pharmacological thromboprophylaxis is widely applied to lower this risk, but guidelines lack dosing recommendations. OBJECTIVE: This survey aims to assess current thromboprophylaxis preferences and willingness to participate in future randomized clinical trials (RCTs) on this topic. METHOD: We conducted an international online survey between February and May 2023 among intensive care unit (ICU) physicians, including 16 questions about preferences in relation to thromboprophylaxis and preferences on topics for a future RCT. The survey was distributed through the network of the Collaboration for Research in Intensive Care. RESULTS: A total of 715 physicians from 170 ICUs in 23 countries contributed information, with a mean response rate of 36%. In most ICUs, both pharmacological (n = 166, 98%) and mechanical thromboprophylaxis (n = 143, 84%) were applied. A total of 36 pharmacological thromboprophylaxis regimens were reported. Use of low-molecular-weight heparin (LMWH) was most common (n = 149 ICUs, 87%), followed by subcutaneous unfractionated heparin (n = 44 ICUs, 26%). Seventy-five percent of physicians indicated that they used enoxaparin 40 mg (4000 IU), dalteparin 5000 IU, or tinzaparin 4500 IU once daily, whereas 25% reported the use of 16 other LMWH type and dose combinations. Dose adjustment according to weight was common (78 ICUs, 46%). Participants perceived high variation in the application of thromboprophylaxis and were willing to consider an alternative LMWH type (n = 542, 76%) or dose (n = 538, 75%) in the context of an RCT. CONCLUSION: LMWH was the preferred agent for thromboprophylaxis in critically ill patients. There was considerable variation in the application of LMWH for prophylaxis, reflected by the use of different types, doses, and dosing strategies. Most physicians would be willing to participate in an RCT on thromboprophylaxis. EDITORIAL COMMENT: This survey demonstrates current patterns in implementation preferences for critically ill patients. While there is one approach and drug that is commonly preferred, these findings show that there is some variation in practice.
Keywords: Surveys and Questionnaires; thromboprophylaxis; Humans; ICU; Female; internacionalita; Venous Thromboembolism; Critical Care; Internationality; lidé; péče o pacienty v kritickém stavu; průzkumy a dotazníky; žilní tromboembolie; Heparin, Low-Molecular-Weight; ženské pohlaví; Male; jednotky intenzivní péče; Practice Patterns, Physicians'; lékařská praxe - způsoby provádění; heparin nízkomolekulární; Intensive Care Units; survey; mužské pohlaví; antikoagulancia; Anticoagulants